2017
DOI: 10.1007/s10585-018-9878-x
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific membrane antigen (PSMA) expression in breast cancer and its metastases

Abstract: The present study was undertaken to investigate the expression of prostate-specific membrane antigen (PSMA) in normal breast tissues, in cancerous breast tissues and in distant metastases from patients with breast cancer. Immunohistochemical analysis was performed to determine PSMA expression and angiogenic activity using anti-PSMA mAb and anti-CD31 mAb respectively. Immunofluorescence staining was applied to confirm the exact co-localization of PSMA and CD31. We observed different patterns of PSMA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 39 publications
0
48
0
12
Order By: Relevance
“…Kasoha et al, reported PSMA expression in healthy breast tissue only on normal glandular cells, while tumorous tissue as well as its metastases showed PSMA expression in tumor cells and in tumor associated neovasculature. Moreover, they confirmed higher PSMA expression in neovasculature of distant metastases than in those of primary tumors [ 26 ]. These findings are also supported by others, reporting PSMA as being highly and specifically expressed in the tumor neovasculature of ovarian, cervical and endometrial cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…Kasoha et al, reported PSMA expression in healthy breast tissue only on normal glandular cells, while tumorous tissue as well as its metastases showed PSMA expression in tumor cells and in tumor associated neovasculature. Moreover, they confirmed higher PSMA expression in neovasculature of distant metastases than in those of primary tumors [ 26 ]. These findings are also supported by others, reporting PSMA as being highly and specifically expressed in the tumor neovasculature of ovarian, cervical and endometrial cancer [ 27 ].…”
Section: Discussionmentioning
confidence: 94%
“…Kasoha et al, observed PSMA to be expressed in the neovasculature of breast tumors and its distant metastases. Interestingly, the 68 Ga-PSMA tracer was strongly uptaken in the bone metastases of a metastatic BC patients, elucidating PSMA as a therapeutic vascular target (10). In the management of PCA, PSMA has already become an attractive target for oncological imaging and radionuclide therapy since its expression persisted in a high percentage of these patients, confirmed by positron emission tomography/computer tomography (58).…”
Section: Discussionmentioning
confidence: 95%
“…Looking for new predictive biomarkers, prostate cancer related markers have been evaluated in TNBC for additional treatment options. In this context, based on findings in prostate cancer (PCA), the prostate specific membrane antigen (PSMA) has become an attractive molecular target for oncological imaging and radionuclide therapy using PSMA PET/CT in TNBC (10,11). In addition, among the different subtypes defined (12), the luminal androgen receptor (LAR) subtype was found to be enriched in mRNA expression of androgen receptor (AR) and several downstream AR targets, resulting in enhanced sensitivity to the AR antagonist bicalutamide (13) which qualifies AR as a suitable target in LAR TNBC.…”
Section: Introductionmentioning
confidence: 99%
“…Several case reports or series have shown the potential of PSMA-targeted imaging in breast cancer among which also cases of TNBC [2426]. A detailed evaluation of the expression on the tumor cells itself and the endothelium of the tumor vessels revealed a higher expression on the endothelium of the tumor vessels, with higher expression rates especially in TNBC in comparison to other breast cancer entities [25, 27]. In this study, we evaluate systematically and show for the first time in vitro and in vivo the potential of targeting of neo-vasculature-associated PSMA by a radiolabeled PSMA-ligand as a promising therapy option in TNBC.…”
Section: Discussionmentioning
confidence: 99%